2019
DOI: 10.1108/ijem-10-2018-0297
|View full text |Cite
|
Sign up to set email alerts
|

A path analysis of diagnosis of organizational levels of functionality

Abstract: Purpose The purpose of this paper is to investigate the extent to which organizational level of functionality is affected by its leadership, its staff, the way task is performed in the organization (culture), and the structural and governance makeup of organizations. This study also determined the direct and indirect impacts of these variables on organizational functionality in general and drawing lessons to educational organizations in specific. Design/methodology/approach This is a quantitative study. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Prudent leaders make decisions based on a detailed examination of present and past conditions, as well as a careful examination of potential possibilities. The researcher has proposed a model and method that allow organizations and their leaders to research (Alemu and Shea, 2019). The methods that may diagnose in an organizational context are the current method to examine organizational status to assess whether improvements are required to improve the organization's performance (Alderfer, 1980).…”
Section: Organizational Functionalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Prudent leaders make decisions based on a detailed examination of present and past conditions, as well as a careful examination of potential possibilities. The researcher has proposed a model and method that allow organizations and their leaders to research (Alemu and Shea, 2019). The methods that may diagnose in an organizational context are the current method to examine organizational status to assess whether improvements are required to improve the organization's performance (Alderfer, 1980).…”
Section: Organizational Functionalitymentioning
confidence: 99%
“…As a result, this study aims to diagnose a newly developed model to investigate the organization's functionality and leadership, employees, the way tasks are carried out (Culture), and organizational structure and governance (Alemu and Shea, 2019). Route analysis, a form of structural equation modeling (SEM), may describe a model that represents the degree and complexity of the effects of the organizational functionality.…”
Section: Organizational Functionalitymentioning
confidence: 99%
“…There are several reviews and theoretical models for diagnosing organizations in the organizational diagnosis literature. Another area of study that uses diagnostic technique is the CSF as a critical organizational success factor (Alemu and Shea, 2019). Lavy et al (2010) suggested that managers should pay attention and diagnose crucial elements that influence the organization's overall performance.…”
Section: Organizational Functionalitymentioning
confidence: 99%
“…Similarly, some previous studies have focused on the role of workers/staff in achieving organizational objectives. Employee care and active engagement are critical for the achievement of organizational objectives (Alemu and Shea, 2019). Amah and Ahiauzu (2013) hypothesized employees' involvement in organizational functionality and discovered a positive connection between productivity of employee and effective organizations.…”
Section: Organizational Functionalitymentioning
confidence: 99%
“…Different diagnostic models can be used in different situations depending on the needs, objectives, and type of organization involved (Appelbaum, 2020). So it is important to choose the right model of diagnosis because a good organization diagnosis will result in the investigation of the best organization (Singh et al, 2017;Alemu & Shea, 2019).…”
Section: Introductionmentioning
confidence: 99%